FORMATION OF SELF-ORGANIZATION OF EDUCATIONAL ACTIVITY OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS - Seryogina І.Ю. (Pedagogy of Higher and Secondary Education, 2022)
In the article the basic of forming of self organization of studying activities of the students in the universities is considered.